Integrating Mindset Interventions with Language Arts Instruction: An Exploratory Study with Seventh Grade Students. Issue 7 (9th August 2017) - Strahan, David; Hansen, Kloo; Meyer, Annie; Buchanan, Ryan; Doherty, Jennifer
Abstract: Researchers engaged in a collaborative, yearlong study with a seventh-grade language arts teacher who integrated activities to enhance students' understanding of mindsets with content instruction. Lessons emphasized four aspects of mindsets: belief that learning abilities can grow with the investment of effort, willingness to address challenging tasks and persevere, development of stronger learning strategies, and ability to articulate connections between effort and accomplishment. During the school year, the team observed lessons, gathered work samples, and conducted interviews with 12 students. Work samples showed that most students articulated a general understanding of the concepts related to mindset emphasized during instruction. Case studies documented patterns and differences in ways students articulated connections among concepts. Although limited by sample size, results suggested that seventh graders can understand the construct of mindsets, especially when offered guidance and support.